The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ma12030431
|View full text |Cite
|
Sign up to set email alerts
|

Single-Composition White Light Emission from Dy3+ Doped Sr2CaWO6

Abstract: A series of Dy3+ ion doped Sr2CaWO6 phosphors with double perovskite structure were synthesized by traditional high temperature solid-state method. It was found that there is significant energy transfer between Dy3+ and the host lattice, and the intensities of emission peaks at 449 nm (blue), 499 nm (cyan), 599 nm (orange), 670 nm (red), and 766 nm (infra-red) can be changed by adjusting the concentration of dopant amount of Dy3+ ion in Sr2CaWO6. The correlated color temperature of Dy3+ ion doped Sr2CaWO6 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Thus, the ratio is greater than 1 for a centrosymmetric site and less than 1 for a noncentrosymmetric site. [ 36,40,47,48 ] In the current case, the peak related to the MD transition of both Eu 3+ ( 5 D 0 → 7 F 1 ) and Dy 3+ ( 4 F 9/2 → 6 H 15/2 ) ions is stronger than the corresponding ED transition of Eu 3+ ( 5 D 0 → 7 F 2 ) and Dy 3+ ( 4 F 9/2 → 6 H 13/2 ) ions. The ratio of intensity of MD/ED transition is found to be 8.85 for Eu 3+ and 6.09 for Dy 3+ ions, indicating that the occupancy of RE 3+ ions is at the centrosymmetric (i.e., A) site in the cubic DP host lattice.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Thus, the ratio is greater than 1 for a centrosymmetric site and less than 1 for a noncentrosymmetric site. [ 36,40,47,48 ] In the current case, the peak related to the MD transition of both Eu 3+ ( 5 D 0 → 7 F 1 ) and Dy 3+ ( 4 F 9/2 → 6 H 15/2 ) ions is stronger than the corresponding ED transition of Eu 3+ ( 5 D 0 → 7 F 2 ) and Dy 3+ ( 4 F 9/2 → 6 H 13/2 ) ions. The ratio of intensity of MD/ED transition is found to be 8.85 for Eu 3+ and 6.09 for Dy 3+ ions, indicating that the occupancy of RE 3+ ions is at the centrosymmetric (i.e., A) site in the cubic DP host lattice.…”
Section: Resultsmentioning
confidence: 59%
“…Thus, the ratio is greater than 1 for a centrosymmetric site and less than 1 for a noncentrosymmetric site. [36,40,47,48] In the current case, the peak related to the MD transition of both Eu 3þ ( 5 D 0 ! 7 F 1 ) and Dy 3þ ( 4 F 9/2 !…”
Section: Pl Studymentioning
confidence: 70%
See 1 more Smart Citation
“…Recently, Mn 4+ -activated Sr 2 ZnWO 6 and LiLaMgWO 6 were investigated as red-far-red phosphors for plant cultivation LEDs. , However, actually, their poor luminescence thermal stability in them makes inappropriate for practical application, which also often takes place in other kinds of Mn 4+ -activated double-perovskite phosphors such as (Ba 1– x Sr x ) 2 YSbO 6 :Mn 4+ , Ca 2 GdSbO 6 :Mn 4+ , Sr 2 YNbO 6 :Mn 4+ , LiLa 2 TaO 6 :Mn 4+ , Ca 2 LaNbO 6 :Mn 4+ , etc., since the working temperature of pc-LEDs can reach above 423 K. Consequently, it is urgent and significant to improve the thermal luminescence quenching performance for current materials or search for novel red-far-red luminescence materials with extraordinary luminescence thermal stability. Recently, Sr 2 CaWO 6 , a double-perovskite compound, was used as a matrix for rare earth (Re 3+ = Dy 3+ , Sm 3+ , Eu 3+ ) ions doping and their luminescence properties were investigated in detail. As mentioned above, there are suitable WO 6 octahedrons in this double-perovskite compound for Mn 4+ incorporation. Unfortunately, we found that the luminescence of Sr 2 CaWO 6 :Mn 4+ is too feeble to be intuitively observable under a 302/365 nm UV lamp irradiation.…”
mentioning
confidence: 65%
“…17–19 According to the literature, some Dy 3+ activated materials show weak red emission around 670 nm due to the 4 F 9/2 → 6 H 13/2 transition. 20 Due to the absence or a weak red color emission, Dy 3+ activated materials show a very poor color rendering index. To solve this problem, Eu 3+ ions can be co-doped in the host material in the presence of the Dy 3+ ion.…”
Section: Introductionmentioning
confidence: 99%